Largely enhanced electrochemical performance in MoO3-x nanobelts formed by a "sauna reaction": Importance of oxygen vacancies. (10th June 2017) - Sun, Zhuangzhi; Yang, Caihong; Liu, Guangyan; Lu, Huibing; Zhang, Rui; Wang, Linjiang; Wang, Hai
Graphical abstract: Schematic illustration of the approach used to prepare MoO3-x Nanobelts via "sauna reaction" process. Highlights: MoO3-x nanobelts with rich oxygen vacancies are rationally synthesized. MoO3-x nanobelts exhibited superior electrochemical performance. OVs concentration could be finely tuned by simply adjusting "Sauna reaction" time. Importance of oxygen vacancies should be considered when designing lithium-ion batteries. Abstract: MoO3–x nanobelts (MoO3-x NBs) were synthesized via a novel "sauna reaction", providing us an opportunity for illustrating the effect of oxygen vacancies (OVs) on its largely enhanced electrochemical performance. Very exciting, the MoO3-x NBs exhibits much superior performance with 400 and 267 mAh g −1, which is about three times larger than that of the pristine MoO3 NBs (123 and 84 mAh g −1 ), at the current densities of 100 and 200 mA g −1, respectively. Notably, the OVs and the resulting improved electrical conductivity could be used to account for their largely enhanced specific capacity and rate properties. On one hand, OVs lowered the energy barrier of Li + into the intralyer of MoO6 octahedron sheet layer and the interlayer of MoO3-x, and provided extra lithium storage sites of MoO3 during discharge-charge process. On the other hand, the improved conductivity of MoO3-x provided efficient electron transport pathways. The results show that OVs control can be a promising strategy for enhancing high-performance Mo-based electrodes by taking advantage of structural characteristics of multiple oxide sates of Mo elements. This study not only provides a new method for the preparation of MoO3-x with rich OVs using a simple, environmentally friendly "sauna reaction", but also indicates the importance of OVs in the largely enhanced electrochemical performance in MoO3-x NBs, which may shed some light on the future development of electrode materials of lithium-ion batteries (LIBs).